The brain symphony for post stroke rehabilitation – A pilot randomised controlled study with P.Ramlee songs / Beh Wen Fen - Beh , Wen Fen (2018)
The interaction between music and the brain involves a complex process, triggering a large network of neurons that includes motor actions, perceptions, and emotions; each part working to process the different aspects of the tune. In terms of the motor areas in the brain, studies revealed that processing music pulses intertwines closely with movement. This research investigates how much effect music has to the brain, in terms of neuroplasticity (where nerve cells adapt to compensate any damage to the brain), especially amongst stroke survivors. The research was conducted in two phases: 1) songs selection process, and 2) medical procedure, in the Department of Rehabilitation University Malaya Medical Centre (UMMC). In the first phase, surveys were conducted to determine the spectrum of popular local songs for subjects aged 55 years old and above, and a playlist of these songs to be played in the second phase. It was discovered that the songs that almost every subject is familiar with and enjoyed are by P. Ramlee. A list of his music was selected to be used for this experiment to test if his songs could have an effect to the subjects. The second phase is an experimental design using music listening on a small sample of 20 subjects aged 55 years old and above and were sorted into stroke survivors and healthy individuals. The subjects were further randomized into two groups: Control group (without music) and Experimental group (with music). The second phase is divided into three stages: Stage one is to pre-screen and select potential subjects before the experiment. The second stage seeks to find the effect of the music selected in phase one on stroke survivors through augmenting the subjects’ brain neuroplasticity through measurement of the mean evoke potential (MEP) using Transcranial Magnetic Stimulation (TMS), and the final stage compares the effects of brain neuroplasticity between lesion and non-lesion areas in the patients. The assessment showed that P.Ramlee’s music does enable brain neuroplasticity. This proves a potential in using music as an adjuvant healing tool for cognitive clinical settings like stroke.